Full-scale experimental investigations on the response of a flooded passenger vehicle under subcritical conditions - Al-Qadami, E.H.H. (Springer Science and Business Media B.V., 2022)
Vehicles can be easily swept away by floodwaters once the flow velocity and depth reach certain critical limits, with probabilities toward fatality reported to be nearly 50. Therefore, understanding the response of the flooded vehicle is necessary in preparing safety guidelines and controlling the risks. In the present work, the hydrodynamic forces on an actual full-scale passenger vehicle being partially submerged and exposed to subcritical flows were investigated. This is one of the earliest works at the present time involving a full-scale vehicle being tested at two orientations, 90Â° and 0Â° and two situations, static and in movement. The drag coefficients were plotted against the Froude number among other hydrodynamic forces. The experimental outcomes revealed that the vehicle positioned at 90Â° orientation with respect to the incoming flows was the critical orientation for both vehicle situations. This is consistent with previous studies based on scale model cars. Besides, drag forces increased significantly with the increment of flow velocity, Froude number, and vehicle speed. Particularly, the flow depth had an accountable effect on the buoyancy, friction, rolling, and driving forces. Under hydrostatic conditions, the vehicle experienced floating instability at 0.40Â m water depth when imposed to an approximate of 11Â kN buoyancy force. Experimental outcomes originated from a full-scale vehicle such as this contribute to new knowledge in supplementing and validating results obtained from the most frequent scaled-model physical testing and numerical modeling. Outcomes obtained from this study will be beneficial in developing a proper safety guideline for vehicle safety. Â© 2021, The Author(s), under exclusive licence to Springer Nature B.V.